A gestão da capacitação baseada na gestão por competência : um estudo da viabilidade de implantação do sistema de capacitação do governo federal na UFES - Cunha, Cristianne Pereira (2014)
The Business Administration since its beginning has developed several management models in order to achieve efficiency. Capacitate, train and develop staff was something essential in most models to achieve desired outcomes. The Brazilian government that for several years looks for a quality and professional public service, published the Decree No. 5.707/2006 that regulates the development of public administration staff. This decree establishes that the Brazilian’s servers development should follow the model of Competency Management. This review verifies, the possibility of implementing this new management model to provide a training program for the Universidade Federal do Espírito Santo (UFES) servers, preparing a project proposal. In this sense takes place a revision of training, skill development, skills and competency management concept. Through its constructs raises the feasibility of implementing a training program that interrelate job requirements, servers skills and the content of training programs its courses offered by the Personnel Development Department at UFES .